The Coronary Circulation as a Target of Cardioprotection. Issue 10 (13th May 2016) - Heusch, Gerd
Abstract : The atherosclerotic coronary vasculature is not only the culprit but also a victim of myocardial ischemia/reperfusion injury. Manifestations of such injury are increased vascular permeability and edema, endothelial dysfunction and impaired vasomotion, microembolization of atherothrombotic debris, stasis with intravascular cell aggregates, and finally, in its most severe form, capillary destruction with hemorrhage. In animal experiments, local and remote ischemic pre- and postconditioning not only reduce infarct size but also these manifestations of coronary vascular injury, as do drugs which recruit signal transduction steps of conditioning. Clinically, no-reflow is frequently seen after interventional reperfusion, and it carries an adverse prognosis. The translation of cardioprotective interventions to clinical practice has been difficult to date. Only 4 drugs (brain natriuretic peptide, exenatide, metoprolol, and esmolol) stand unchallenged to date in reducing infarct size in patients with reperfused acute myocardial infarction; unfortunately, for these drugs, no information on their impact on the ischemic/reperfused coronary circulation is available.